The Influence of Overconfidence, Disposition Effect, and Risk Aversion on Sharia Stock Investment Decisions with Financial Literacy as a Moderating Variable (A Study on Investors of KSPM-GIS UIN Raden Mas Said Surakarta): Pengaruh sikap terlalu percaya diri, efek disposisi, dan penghindaran risiko terhadap keputusan investasi saham syariah dengan literasi keuangan sebagai variabel moderating - Biyati, Biyati; Imanda Firmantyas Putri Pertiwi (Social Science Studies, 2024)
Research Aims: This study aims to examine the influence of overconfidence, disposition effect, and risk aversion on Sharia stock investment decisions, with financial literacy as a moderating variable. Design/methodology/approach: This research employs a quantitative method with primary data. The sampling technique utilized is purposive sampling, involving a sample size of 350 respondents. The analysis technique for this study employs moderated regression analysis. Research Findings: The results of this study indicate that overconfidence and financial literacy have a positive and significant influence on Sharia stock investment decisions. However, disposition effect and risk aversion do not significantly affect Sharia stock investment decisions. Financial literacy does not moderate the relationship between overconfidence and disposition effect on Sharia stock investment decisions. However, it does moderate the relationship between risk aversion and Sharia stock investment decisions. Theoretical Contribution/Originality: This thesis provides insights into the relationships between overconfidence, disposition effect, risk aversion, and financial literacy concerning Sharia stock investment decisions. These findings can serve as a reference or valuable insight for investors, institutions, and stakeholders interested in optimizing their investment decision-making processes. Keywords: Overconfidence, disposition effect, risk aversion, investment decision, financial literacy